Potential role of salivary vitamin D antimicrobial peptide LL-37 and interleukins in severity of dental caries: an exvivo study - Nireeksha; Mithra N Hegde; Suchetha Kumari N (BMC, 2024)
Abstract Introduction Vitamin D performs various functions as a hormone by promoting calcium absorption but plays a major role in innate immunity,cell differentiation, cell maturation through its genomic effects via vitamin D receptor. The immune response also plays a major role in tooth surface and supporting structure destruction and playing a major factor in high caries formation. The inflammatory cytokines are released has proinflammatory cytokines and stimulate cells in disease process. Therefore, in the present study we have evaluated the association of salivary vitamin D, LL-37, interleukins 6 and 17A in various levels of severity of dental caries. Method Ethical approval was obtained (NU/CEC/2020/0339), 377 individuals reporting to department of conservative dentistry and endodontics, AB Shetty memorial institute of dental sciences were included based on inclusion criteria. The individuals were further divided into caries free(N = 105) and caries active(N = 272) based on their caries prevalence. The salivary were collected and evaluated for vitamin D, LL-37,IL-17A and IL-6.Results were statistically analysed with SPSS vs 22 (IBM Corp, USA). Normally distributed data were expressed as mean ± SD. Skewed data were expressed as median and interquartile range. To compare (mean) outcome measures between the two groups unpaired independent t-test was applied and for values in median IQR, Mann Whitney U test was used. All statistical analysis for P value were two-sided and significance was set to P ≤ 0.05. Results The study showed that, the salivary vitamin D statistically decreased with increasing severity of caries which showed that vitamin D plays an important role in prevention of caries. Antimicrobial peptide LL-37 was higher in caries free group but was not statistically significant, salivary IL-6 level was higher in caries active group but intergroup comparison did not show significant difference. Salivary IL-17A did not show statistically significant between caries active and caries free group. Conclusion The salivary levels of vitamin D may play a vital role in prevalence of dental caries and its severity which can be a underlying cause in presence of other etiological factors.